Feasibility of Tai Chi intervention for improving quality of life in older adults with gait disorders: a pilot study - Xu, Fan; Soh, Kim Geok; Chan, Yoke Mun (Human Resources Management Academic Research Society (HRMARS), 2024)
Maintaining older adults' health and quality of life (QoL) is increasingly important with the global population ageing. Gait disorders can lead to reduced mobility and a heightened risk of falls, significantly impacting the overall well-being of older adults. Tai Chi (TC), a traditional Chinese martial art, is recognised for its potential to improve balance, strength, and mobility, which may, in turn, positively influence the QoL in older adults. This pilot study aimed to evaluate the feasibility and effectiveness of a TC intervention on the QoL of older adults with gait disorders. Recruited 16 participants and conducted a two-week training session. QoL was assessed using the SF-36 questionnaire, with validity and reliability evaluated through the content validity index (CVI) and expert ratings. All statistical analyses were conducted using SPSS version 20.0. Content validity analysis indicated strong correlations among SF-36 items (CVI = 0.833, kappa = 0.816), and internal consistency across dimensions was high (Cronbach’s alpha ranged from 0.846 to 0.970). Despite high retention and compliance rates, there were no significant improvements in overall QoL scores post-intervention. This study demonstrates the feasibility and acceptability of a TC intervention for older adults with gait disorders. Although no significant changes in QoL were observed, the findings suggest that further research with extended interventions is warranted to explore the potential benefits of TC for this population.